(untitled) (The Review of Diabetic Studies, 2025)
The Iron Age in Tamil Nadu represents a critical phase of cultural and technological advancement, marked by the transition from a Neolithic subsistence economy to a more complex society rooted in agricultural surplus and urbanization. This period, corresponding to the rise of megalithic culture, witnessed the construction of monumental burial structures and the refinement of iron tools, significantly impacting settlement patterns and social organization. The Salem region, rich in megalithic sites such as dolmens, cairn circles, cist burials, and urns, provides invaluable insights into the burial and funerary practices of the time. Literary evidence, particularly from Sangam literature, corroborates archaeological findings, revealing a profound belief in the afterlife and the social significance of hero stones. This study synthesizes archaeological and literary data to examine the megalithic remains in Salem, emphasizing their role in shaping the cultural and historical landscape of Iron Age Tamil Nadu.